Vestibular schwannoma inducing unilateral tinnitus and auditory impairment: A literature review - Setiawan, Gunawan Wijaya (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Vestibular schwannoma (VS) is a noncancerous tumor of the vestibulocochlear nerve that usually causes ringing in the ears and hearing loss in one ear. Modern clinical challenges extend beyond mere tumor eradication to encompass the early identification of retrocochlear disease, safeguarding functional hearing, managing tinnitus-related disorders, and choosing treatment approaches that maintain facial nerve function and enhance quality of life. Methods: This literature review integrates the most recent evidence regarding epidemiology, clinical presentation, diagnostic assessment, natural history, observation, stereotactic radiotherapy, microsurgery, tinnitus outcomes, and auditory rehabilitation. Results: Recent guidelines, cohort studies, systematic reviews, and meta-analyses all point to MRI of the internal auditory canal as the best way to diagnose asymmetric hearing loss or suspicious unilateral audiovestibular symptoms. Small tumors that don't affect hearing are often good candidates for active surveillance, but hearing can get worse even when the tumor isn't growing much on imaging. Radiosurgery offers lasting tumor control for specific small to medium-sized tumors, although long-term preservation of hearing diminishes over time. Microsurgery is still important for big tumors, brainstem compression, radiosurgery failure, or certain patient needs. However, keeping hearing is very dependent on the patient's hearing before the surgery, the size of the tumor, the approach used, and the monitoring done during the surgery. Tinnitus is prevalent, clinically significant, and not entirely predictable by tumor size or treatment approach. Conclusion: The literature endorses a personalized, multidisciplinary methodology that incorporates audiometry, MRI-based surveillance, patient-reported outcomes, and collaborative decision-making.